Vigilance Degree Computing Based on EEG - Zhenzhong Zhan; Zhendong Mu (Institute of Advanced Engineering and Science, 2013)
In daily life, lots of work need people maintain higher attention or vigilance. In the early study of vigilance, blink frequency, the impedance of skin, body temperature and blood pressure and other physiological signals was used to estimate the vigilance. EEG signal can more directly reflect the brain's activity than other physiological signals, and EEG signal have a higher time resolution. In this paper, ERP component and different frequencies of EEG were used to analyze the alert state, according to this study, in the ERP components, N170 can be a good representation of the degree of fatigue of the subject; Through the 10 subjects EEG frequency distribution analysis, and according to the formula defined in this paper, the vigilance degree of this ten subjects was calculated. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3298